Respuestas

  • Usuario de Brainly
2013-12-13T18:24:24+01:00
[3 - 4/5 ÷ (1-3/4) +2] x 1/3 - 2/5 ÷ 3 -1/4

* (1-3/4) = (4/4  - 3/4) = (4-3)/4 = 1/4
* 2/5÷ 3 = (2/5) x (1/3) = 2/15

[3 - 4/5 ÷ (1/4) +2] x 1/3 - 2/15 -1/4

* 4/5 ÷ 1/4 = 4/5 x 4/1 = 16/5

[ 3 - 16/5 + 2 ] x (1/3) -  (2/15 + 1/4)

* 3+2 =5
* 2/15 + 1/4 =  (2x4 + 15x1)/(15x4) = (8+15)/(60) = 23/60

[ 5 - 16/5] x (1/3) -  (23/60)

* 5-16/5 =( 5(5) - 16) / 5 = (25 - 16)/5 = 9/5

[ 9/5] x (1/3) -  (23/60)

9/15 - 23/60

4(9)/4(15) - 23/60

36/60 - 23/60

13/60 = Solucion